Rancang Bangun Game Edukasi Pengenalan Profesi Berbasis Multimedia Sebagai Media Pembelajaran Untuk Siswa SD - Septanto, Henri; Ari Hidayatullah (KALBISCIENTIA Jurnal Sains dan Teknologi, 2025)
Education in elementary school plays an important role in shaping children's knowledge, attitudes and skills. One aspect that needs to be considered in education is introduction to various professions, because it can increase insight into various career options in the future. This research aims to introduce several professions to children through educational games. This educational game application is designed to provide a fun learning experience, where students can learn while playing. The software development method used is the Game Development Life Cycle, including pre-production, production, testing, launch and evaluation stages. Each stage is carried out carefully to ensure the resulting application meets educational needs effectively and attractively. The targeted output of this research is an educational game prototype for elementary school students, as well as articles published in SINTA accredited journals. The result of this research is an educational game application that is able to increase students' understanding of various professions so that it can motivate them to try to achieve their dreams.